HUBUNGAN TRANSFER PRICING DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2016-2020 - Dela Ayu Putranti; Vidiyanna Rizal Putri (Journal of Accounting, Management and Islamic Economics, 2023)
The purpose of this research is to analyze the relation of Transfer pricing, financial distress on Tax avoidance and audit quality as moderating variable. This study uses data from 40 banking companies listed on the Indonesia Stock Exchange in the period of 2016-2020. This research method uses secondary data with a sampling method in te form of purposive sampling. The hypotheses in this study were tested with descriptive statistics and multiple regression methods. The results of this study indicate that Transfer pricing have a positif and signifikan. Financial distress have a positive and significant effect. Audit quality have a positive and significant effect on Tax avoidance. Audit quality is able to weaken the result of Transfer pricing and financial distress on Tax avoidance.